Design and Synthesis of Hydrolytically Stable N‐Nitrourea Explosives. Issue 6 (28th July 2015) - Cui, Kejian; Xu, Zhibin; Xu, Guangrui; Meng, Zihui; Liu, Wenjin; Shi, Xinpeng; Xu, Yudong; Li, Jiarong; Lin, Zhihui
Abstract: A series of high energy density compounds (HEDCs) based on N‐nitrourea were designed and their theoretical performances were calculated using the Gaussian programs. The predicted values of the energy density of these compounds are in the range 1.848–1.93 g cm −3, and their calculated VODs are in the range 6700–8305 m s −1 . Tetranitrodiglycoluril (TNDGU) (1 ) and tetranitrotriglycoluril (TNTGU) (2 ) were synthesized and characterized by NMR ( 1 H, 13 C) and IR spectroscopy as well as elemental analyses. The structure of the aminolysis product (7 ) of TNDGU was further confirmed by single‐crystal X‐ray diffraction, which indicated that the structure belongs to P 21 / c space group in the monoclinic system. Abstract :